Reinnervation of Vastus lateralis is increased significantly in seniors (70-years old) with a lifelong history of high-level exercise (2013, revisited here in 2022) - Simone Mosole; Katia Rossini; Helmut Kern; Stefan Löfler; Hannah Fruhmann; Michael Vogelauer; Samantha Burggraf; Martina Grim-Stieger; Ján Cvečka; Dušan Hamar; Milan Sedliak; Nejc Šarabon; et al. (PAGEPress Publications, 2022)
In 2013 we presented results showing that at the histological level lifelong increased physical activity promotes reinnervation of muscle fibers in aging muscles. Indeed, in muscle biopsies from 70-year old men with a lifelong history of high-level physical activity, we observed a considerable increase in fiber-type groupings (F-TG), almost exclusively of the slow type. Slow-type transformation by denervation-reinnervation in senior sportsmen seems to fluctuate from those with scarce fiber-type transformation and groupings to almost fully transformed muscle, going through a process in which isolated fibers co-expressing fast and slow Myosin Heavy Chains (MHCs) seems to fill the gaps. Taken together, our results suggest that, beyond the direct effects of aging on the muscle fibers, changes occurring in skeletal muscle tissue appear to be largely, although not solely, a result of sparse denervation-reinnervation. The lifelong exercise allows the body to adapt to the consequences of the age-related denervation and to preserve muscle structure and function by saving otherwise lost muscle fibers through recruitment to different, mainly slow, motor units. These beneficial effects of high-level life-long exercise on motoneurons, specifically on the slow type motoneurones that are those with higher daily activity, and on muscle fibers, serve to maintain size, structure and function of muscles, delaying the functional decline and loss of independence that are commonly seen in late aging. Several studies of independent reserchers with independent analyses confirmed and cited our 2013 results. Thus, the results we presented in our paper in 2013 seem to have held up rather well.